Re-Imagining Screen and Stage in a Human Rights-Centered Curriculum - Werth, Brenda (Latin American Theatre Review, 2017)
This essay explores the benefits of teaching and learning Latin American theatre in dialogue with film. Specifically, I discuss the dialogue between documentary modes of performance in the context of interdisciplinary courses on human rights and the arts that I have designed and taught in a Latin American studies program at American University. In my courses, I introduce theatre as a fundamental paradigm for understanding the collective, embodied, and intersubjective formations of human rights movements and action. Recent Latin American documentary theatre and film reveal a rich cross-pollination between genres; plays frequently incorporate documentary film footage, while many documentary films have become more theatrical or performative in nature. In this essay I show how studying documentary Latin American theatre and film in tandem can deepen and enhance an understanding of how these genres shape new modes of self-expression and activism, unsettle divisions between fact and fiction, advance and question existing forms of truth-telling, contribute new archives of knowledge, and engage discourses of memory, history, and human rights. I begin the essay by offering a theoretical framework and pedagogical rationale for learning and teaching documentary theatre in conjunction with documentary film. At the end of the essay, I propose the pairing of two Argentine works—Albertina Carri’s film Los rubios (2003) and Lola Arias’ play Mi vida después (2009)—as a case study for how to approach the joint teaching of documentary film and theatre.